ANTIBACTERIAL PROPERTIES OF LEUCAS CEPHALOTES (ROTH) SPRENG. LEAF - Madhukiran, B.L. (Medknow Publications & Media Pvt Ltd, 2002)
Leucas cephalotes a common ethanomedicinal plant, is used by folklore of Tirupati in Andhra Pradesh for fevers and urinary tract infections. In the present study leaves of L. cephalotes were shade dried, powerdered and extracts were made by Soxhlet Extractor using different organic solvents like hexane, dichloromethane, methanol and ethylacetate. The antimicrobial activity of these organic extracts was evaluated against pathogenic organisms of staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris and Klebsiella pneumoniae. These isolates were obtained from clinical specimens like urine, blood and pus of Sri Venkateshwara Institute of Medical Sciences, Tirupati. The zone of inhibition was determined for these pathogenic microorganism by using specific standards and respective controls for determining Minimum inhibitory Concentration (MIC). Among these tested organic extracts, hexane and methanolic extracts showed prominent antibacterial activity index for each tested extract has been calculated.